Suppression of osteoblast-related genes during osteogenic differentiation of adipose tissue derived stromal cells. Issue 1 (January 2017) - Açil, Yahya; Ghoniem, Amir Alexander; Gülses, Aydin; Kisch, Tobias; Stang, Felix; Wiltfang, Jörg; Gierloff, Matthias
Abstract: Recent studies indicated a lower osteogenic differentiation potential of adipose tissue-derived stromal cells (ASCs) compared to bone marrow derived mesenchymal stromal cells. The aim of this study was to evaluate the effects of potent combinations of highly osteogenic bone morphogenetic proteins (BMPs) in order to enhance the osteogenic differentiation potential of ASCs. Human ASCs were cultured for 10 days in the presence of osteogenic medium consisting of dexamethasone, ß-glycerophosphate and ascorbat-2-phosphate (OM) supplemented with BMP-2, BMP-6, BMP-9+IGF-2 and BMP-2, -6, -9 (day 1+2: 50 ng/ml, days 3–6: 100 ng/ml, days 7–10: 200 ng/ml). The formation of the osteoblast phenotype was evaluated by quantification of osteoblast-related marker genes using real-time polymerase chain reaction (RT-PCR). Matrix mineralization was assessed by Alizarin Red S staining. Statistical analysis was carried out using the one-way analysis of variance (ANOVA) followed by the Scheffe's post hoc procedure. Osteogenic medium (OM) significantly increased the expression of alkaline phosphatase (ALP) and osteocalcin (p < 0.05) and led to a stable matrix mineralization. Under the influence of BMP-9+IGF-2 and BMP-2, -6, -9 the ALP expression further increased compared to ASCs cultured with OM only (p < 0.01). However, multiple osteogenic markers showed no change or decreased under the influence of OM and BMP combinations (p < 0.05). The current results indicate a restricted osteogenic differentiation potential of ASCs and suggest careful reconsideration of their use in bone tissue engineering applications.